Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi, dan Motivasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. PLP Indonesia - Yudi Hendriawan; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
The purpose of this study was to analyze effect of tranformational leadership style, organizational culture and employe motivation to employe performance mediated by job performance at PT. PLP Indonesia. The data were obtained from 179 employees working at PLP Indonesia were selected as respondents using proportionate stratified random sampling. The data were analyzed by multiple linear regression methods and path analysis which was operated through SPSS Software. The results of this study indicated that Transformational leadership style has no significant effect on job satisfaction (1) and employees’ performance (4). Organizational culture has significant effect on employees’ job satisfaction (2) and employees’ performance (5). Motivation has significant effect on employees’ job satisfaction (3) and meanwhile no significant effect on employees’ performance (6). Job satisfation has significant effect on employees’ performance (7). Job satisfaction mediates the influence of tranformational leadership style (8) and the influence of organizational culture (9) has no significant effect on employees’ performance. Job satisfaction mediates the influence of work motivations on employees’ performance significantly (10). Transformational leadership style, organizational culture, and motivation simultaneously affect on job satisfaction (11) and affect on employees’ performance (12).